2020
DOI: 10.1098/rsos.190704
|View full text |Cite
|
Sign up to set email alerts
|

Does repeatedly viewing overweight versus underweight images change perception of and satisfaction with own body size?

Abstract: Body dissatisfaction is associated with subsequent eating disorders and weight gain. One-off exposure to bodies of different sizes changes perception of others' bodies, and perception of and satisfaction with own body size. The effect of repeated exposure to bodies of different sizes has not been assessed. We randomized women into three groups, and they spent 5 min twice a day for a week completing a one-back task using images of women modified to appear either under, over, or neither over- nor underweight. We… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 41 publications
1
7
0
Order By: Relevance
“…Several authors have suggested that adaptation may serve as a laboratory model of, a treatment for, or even the cause of real-world examples of body image distortion (Winkler and Rhodes, 2005 ; Glauert et al, 2009 ; Hummel et al, 2012b ; Brooks et al, 2016 ; Mohr et al, 2016 ; Challinor et al, 2017 ; Stephen et al, 2018 ; Bould et al, 2020 ). However, the discrepancy between results in adaptation studies and those in clinical studies may appear to cast doubt on these claims.…”
Section: Adaptation In Real-world Cases Of Body Image Distortionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several authors have suggested that adaptation may serve as a laboratory model of, a treatment for, or even the cause of real-world examples of body image distortion (Winkler and Rhodes, 2005 ; Glauert et al, 2009 ; Hummel et al, 2012b ; Brooks et al, 2016 ; Mohr et al, 2016 ; Challinor et al, 2017 ; Stephen et al, 2018 ; Bould et al, 2020 ). However, the discrepancy between results in adaptation studies and those in clinical studies may appear to cast doubt on these claims.…”
Section: Adaptation In Real-world Cases Of Body Image Distortionmentioning
confidence: 99%
“…These studies have been replicated many times, with researchers falling into two camps. For evidence of perceptual overestimation, those with a background in clinical psychology point to the selection of larger matching bodies (Slade, 1985 ; Cash and Deagle, 1997 ; Farrell et al, 2005 ; Gardner and Brown, 2014 ; Mölbert et al, 2017 ), while experts in perception offer examples of smaller matching bodies (Winkler and Rhodes, 2005 ; Glauert et al, 2009 ; Hummel et al, 2012a , b ; Mohr et al, 2016 ; Stephen et al, 2016 , 2018 ; Ambroziak et al, 2019 ; Bould et al, 2020 ; Zopf et al, 2021 ). How can these opposite patterns of results be described using the same terminology?…”
Section: Introduction: the Paradox Of Body Size Estimationmentioning
confidence: 99%
“…Our result is coherent with the conclusions reached by Ambroziak et al [16], who failed to find any specific alteration of perceptual body image in the same forced choice task. Similarly, Bould et al [17] found no own-body overestimation after repeated exposure to thin bodies during 5 min, twice a day, for a week. On the contrary, participants responded to this procedure as if they underestimated their own size (or overestimated the size of test stimuli).…”
Section: Discussionmentioning
confidence: 99%
“…Our findings have important implications for researchers in the field of body size perception and body image disturbance. As previously stated, the vast majority of previous research has presented stimuli as 2D (e.g., Alexi et al, 2018; Bould et al, 2020; Cornelissen et al, 2016; Mohr et al, 2016; Rodway et al, 2019; Vocks et al, 2009). Often such paradigms require participants to judge the size of a 2D body image (e.g., Alexi et al, 2018; Alexi, Palermo, et al, 2019) or manipulate the 2D appearance by stretching the images horizontally (e.g., Sand et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…One seemingly important basic consideration that has received little attention is the physical representation of the body being judged by the participant in the test setting. The vast majority of research on body size judgements utilises bodies that are presented as two-dimensional (2D) images on a flat panel display (e.g., Alexi et al, 2018; Bould et al, 2020; Cornelissen et al, 2016, 2018, 2021; Groves et al, 2019; Mohr et al, 2016; Rodway et al, 2019; Vocks et al, 2009). However, this presentation method reduces the appearance of a body from being a three-dimensional (3D) volume (its natural state), to a 2D surface area.…”
mentioning
confidence: 99%